Óleos essenciais como antimicrobianos naturais em pós-colheita de frutos - Rodrigues, Camila Bueno (Universidade Federal de São Carlos, 2022)
Essential oils (OEs) present antimicrobial activity and can be used as natural compounds to inhibit bacteria and fungi. This study aimed to evaluate the OEs potential to control microorganisms that could cause food spoilage. OEs from Mentha spicata, Cymbopogon martinii and the essential oil from Eugenia caryophyllus were commercially obtained. These substances were evaluated to observe the antimicrobial ability to inhibit Penicillium spp., Staphylococcus aureus and Escherichia coli. Data indicated the potential utilization of OEs to control bacteria and fungi. The best OEs results were found with Eugenia caryophyllus and Cymbopogon martinii with high fungi inhibition (250µL and 750µL, respectivelly). On the other hand, Eugenia caryophyllus presented antibacterial inhibition against Staphylococcus aureus. Mentha spicata presented the best MIC and MBC (0,781 and 3,125) to Escherichia coli and Staphylococcus aureus, respectivelly.
Essential oils as natural antimicrobials in fruits post-harvest
Keywords: Óleos essenciais; Atividade antimicrobiana; Pós-colheita; Penicillium; Essential oils; Staphylococcus aureus; Escherichia coli; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA